Dimensões da gestão escolar: saberes e prática do diretor de escola - Silva, Camila Godói da (2015)
The aim of this study is to investigate the relationship between the different dimensions of School Management - practice, conception and knowledge of the School Headmaster - in the context of the municipal education system, in the city of Itapevi, in the state of São Paulo, Brazil. The research question of this study was defined as follows: What is the necessary knowledge for a municipal school headmaster to develop an effective practice, taking into consideration the different dimensions of school management? This thesis also aimed at (1) identifying the necessary knowledge for the practice of a school headmaster - his or her actions, significance, conceptions, motivations and implications regarding the dimensions of school management; (2) stimulating reflection amongst headmasters, thus contributing to a new perspective vis-à-vis their professional activity, and also, to future professional development programmes for them. In order to conduct the investigation and ensure that the objectives were achieved, this research drew on a qualitative survey, with a focus on bibliographical investigation, document analysis and field research. After the field research, a questionnaire was designed and distributed with a view to establish the profiles of the school and the headmaster, and thus, proceed with the selection of the research subjects municipal school headmasters from the city of Itapevi São Paulo with whom in-depth interviews were also carried out. Through a historical-documentary data collection in the municipality, it was possible to identify the legal attributes of the position. The development of the methodological procedures was based on the contributions of Chizzotti (2013), Laville e Dionne (1999), amongst others. The theoretical foundation of this research was supported by authors such as: Alonso (1983), Sander (2007), Paro (2010), Lück (2009, 2010), Apple e Beane (2001), Brito (1998, 2011 e 2014), Sacristán (1995), Freire (1986, 2005 e 2007), Masetto (2004), Lazzarin, besides Tardif (2014). Federal, State and Municipal Legislation related to the school headmaster position was also used as theoretical parameters in this study. There was also a National Management Reference Prize, from the Quality Programme, under the joint coordination of UNICEF, INEP, the Ministry of Education and the School s Development Plan, which also featured amongst the documents surveyed. The importance of the dimensions concerned to the practice of the school headmaster, which are: Pedagogical Management, Educational Results Management, Democratic and Participative Management, Administrative Management, People Management, School Climate and Culture, as well as the relevance of this study to future programmes of continuous professional development for them, are some of the conclusions of this investigation